1989
DOI: 10.1111/j.1365-2621.1989.tb08596.x
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Properties of Sago Starches with Low and High Viscosities on Amylography

Abstract: Both amyloses and amylopectins from sago starches with low (280 BU, low‐v) and high (735 BU, high‐v) viscosities on amylography differed in molecular structures. The low‐v amylopectin (average chain length, c.I., 22) was a smaller molecule with a slightly higher amount of long chains than the high‐v amylopectin (c.I., 22). The number‐and weight‐average degrees of polymerization of the low‐v amylose were 2490 and 5090, respectively, which were half those of the high‐v amylose. The low‐v amylose had a lower mola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“…The same observation was reported by Huber & BeMiller [8], Benmoussa et al [22] and Singh et al [23]. The pin holes appeared due to the action of amylases during the growth of sorghum grain or the starch isolation process [24].…”
Section: Morphological Propertiessupporting
confidence: 83%
“…The same observation was reported by Huber & BeMiller [8], Benmoussa et al [22] and Singh et al [23]. The pin holes appeared due to the action of amylases during the growth of sorghum grain or the starch isolation process [24].…”
Section: Morphological Propertiessupporting
confidence: 83%
“…The structure of amylopectin has been reported to play an important role in the pasting properties of starches. An increase in molecular weight of amylopectin has been effete to decrease the amount of long-branch chain length as well as branching degree of amylopectin, which affected to an increase with peak viscosity and breakdown and decrease in setback and final viscosity (Takeda et al 1989). …”
Section: Resultsmentioning
confidence: 99%
“…Dynamic viscoelastic methods can provide an excellent tool for studying rheological changes during heating and cooling without breaking the stucrure [74] . Many studies have reported the (amylographic) viscosity of sago starch [75][76][77][78] and relatively few have applied any rheological model to the shear stress-shear rate or viscosity-speed behaviour of the starch [14,79] . The rheological behaviour of six sample of sago starch of 4% (w/w) paste were studied at 30°C, 40°C, 50°C, 60°C and 70°C and it was found that the rheological and viscosity of were inversely related to the temperature and they showed different temperature sensitivity but their granules are essentially identical in size and configuration [80] .…”
Section: Rheological Behaviour Of Sago Starhmentioning
confidence: 99%